WNK4 is an essential effector of anterior formation in FGF signaling - Shimizu, Masahiro (Blackwell Publishing Ltd, 2013)
With no lysine (K) (WNK) kinase family is conserved among many species and regulates SPAK/OSR1 and ion cotransporters. WNK is also involved in developmental and cellular processes, but the molecular mechanisms underlying its regulation in these processes remain unknown. In this study, we found that WNK4 is involved in fibroblast growth factor (FGF) signaling during Xenopus development. In Xenopus embryos, depletion of WNK4 by antisense morpholino oligonucleotides (MOs) results in a severe defect in anterior development and impaired expression of endogenous anterior markers. Defects in head formation or expression of anterior marker genes caused by suppression of endogenous WNK4 expression could be rescued by expression of wild-type WNK4, but not mutant WNK4 lacking its kinase activity. It is notable that morphants of Xenopus WNK4 inhibited the expression of anterior marker genes and the target genes induced by FGF signaling. Moreover, knockdown of Wnk4 significantly reduced the phosphorylation level of Osr1 induced by FGF. These results provide the first evidence that FGF signaling regulates WNK4 function required for anterior formation in Xenopus development.